Dyskusja wokół reformy ustroju Rzeczpospolitej Obojga Narodów w kontekście 230. rocznicy uchwalenia Konstytucji 3 maja – materiały źródłowe w zbiorze książnicy bydgoskiej (Tabularium Historiae, 2020)
2021 will be the 230th anniversary of the May 3rd Constitution. In connection with the jubilee, the resources of the Provincial and Municipal Public Library in Bydgoszcz were reviewed in search of collections related to the discussion on the reform of the Polish-Lithuanian Commonwealth and the adoption of the constitution. The selected library units included eighteenth-century manuscripts and prints, as well as iconographic, cartographic and social materials. The collection consists of six parts, concerning such issues as: the political system of the state and attempts to improve it, with particular emphasis on the deliberations of the Grand Seym, the adoption of the Constitution and the fall of the Republic of Poland, the tradition of the Constitution of May 3.